2015
DOI: 10.5901/mjss.2015.v6n3p371
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Boko Haram Terrorism on Northern Nigeria

Abstract: Terrorism has been a global menace which affects economic, political and social status of the country experiencing it. The political dimension of terrorism and insecurity have been examined in this study which moribund political regime of President Goodluck Jonathan in Nigeria. Many lives and properties have been destroyed in Northern Nigeria by the Boko Haram deadly attacks. It is evident from this study that Boko Haram terrorist insurgency invigorated as a result of pronouncement of Goodluck Jonathan as pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…In a study carried out by Chukwurah et al (2015), it was found out that before the emergence of the Boko Haram group, the economy of the north was vibrant and bubbling. This was crucial as a sort of synergy is needed between the economies of all the regions of Nigeria for the country to truly develop in a peaceful and secure manner.…”
Section: Peace and Security Implications Of Boko Haram Terrorist Activitiesmentioning
confidence: 99%
“…In a study carried out by Chukwurah et al (2015), it was found out that before the emergence of the Boko Haram group, the economy of the north was vibrant and bubbling. This was crucial as a sort of synergy is needed between the economies of all the regions of Nigeria for the country to truly develop in a peaceful and secure manner.…”
Section: Peace and Security Implications Of Boko Haram Terrorist Activitiesmentioning
confidence: 99%
“…Evidence in support of the foregoing argument shows that the "net deaths attributed to Boko Haram increased by 317 per cent in 2015, thereby upgrading the jihadist death tolls to 6 644, as against ISIL's death record in 2014, which accounted for about 6 073 terrorist deaths" (GTI, 2015). Chukwurah et al (2015) have described Boko Haram terrorism as the deliberate and systematic use of violence to destroy, kill, maim and intimidate innocent citizens in order to achieve a goal or to draw national or international attention to their demands, which may be impossible or difficult to achieve through normal political negotiation or on the battle field against the government's army. (p. 13) Terrorism, whether globalized or localized, can be said to be politically or socio-economically inclined, although it might reflect some other auxiliary undertones such as religious, socio-ethnic, or cultural motives.…”
Section: Introductionmentioning
confidence: 99%
“…In Nigeria, Boko Haram has destabilized government activities largely in northeastern part of Nigeria. Chukwurah et al (2015) and Nnamdi et al (2015) noted that in the northeastern part of Nigeria, lives have been lost and properties damaged due to various activities of Boko Haram. The persistent insecurity risk posed by the Boko Haram sect has greatly affected the growth of tourism in the Yankari Game Reserve as a result of gross insecurity.…”
Section: Introductionmentioning
confidence: 99%